2006
DOI: 10.1111/j.1742-4658.2006.05551.x
|View full text |Cite
|
Sign up to set email alerts
|

Mutational analysis of substrate recognition by human arginase type I − agmatinase activity of the N130D variant

Abstract: Upon mutation of Asn130 to aspartate, the catalytic activity of human arginase I was reduced to ∼ 17% of wild‐type activity, the Km value for arginine was increased ∼ 9‐fold, and the kcat/Km value was reduced ∼ 50‐fold. The kinetic properties were much less affected by replacement of Asn130 with glutamine. In contrast with the wild‐type and N130Q enzymes, the N130D variant was active not only on arginine but also on its decarboxylated derivative, agmatine. Moreover, it exhibited no preferential substrate speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 36 publications
1
26
0
Order By: Relevance
“…It is interesting to compare these results with those reported in previous studies of the more conservative N130D and N130Q mutants of human arginase I (48). Presuming that the D130 side chain can function in the protonated form as a carboxylic acid, both D130 and Q130 could preserve a hydrogen bond interaction with the α-carboxylate of the substrate.…”
Section: Resultsmentioning
confidence: 54%
See 1 more Smart Citation
“…It is interesting to compare these results with those reported in previous studies of the more conservative N130D and N130Q mutants of human arginase I (48). Presuming that the D130 side chain can function in the protonated form as a carboxylic acid, both D130 and Q130 could preserve a hydrogen bond interaction with the α-carboxylate of the substrate.…”
Section: Resultsmentioning
confidence: 54%
“…Perhaps this reflects the evolutionary potential of N130 and its associated loop 4 as a “hot spot” in the evolution of substrate specificity as noted by Carvajal (48), given that the arginase fold is shared by agmatinase (31). Intriguingly, Carvajal further reports that although N130D human arginase I exhibits 9-fold diminished substrate affinity with l -arginine, this mutation confers agmatinase activity with K M and k cat values of 1.4 mM and 3 s −1 , respectively (48). These values compare with K M and k cat values values of 1.5 mM and 140 s −1 , respectively, measured for wild-type agmatinase from Escherichia coli (51).…”
Section: Discussionmentioning
confidence: 75%
“…The question remains as to what effects, if any, these polypeptide insertions have on arginase structure and function? Kinetic measurements on a PFA construct bearing a C-terminal streptavidin affinity tag initially suggested that malarial arginase is less catalytically efficient than the mammalian arginases, with k cat / K M = 7.4 × 10 3 M −1 s −1 (21) (compared with k cat / K M = 2.0 × 10 5 M −1 s −1 for rat arginase I (27) or 1.27 × 10 5 M −1 s −1 for hAI (28)).…”
mentioning
confidence: 99%
“…Of the 19 rate constants in our model, we have explicit literature values for k C 2-IR , k A 1-IR , and γ C (Mansuy and Boucher 2004; Alarcón et al 2006; Kolodziejski et al 2004). Additionally there exist literature values for k C 1-IRrep , K C 1rep , K C 2 , K A 1 , and K i (Mansuy and Boucher 2004; Alarcón et al 2006; Boucher et al 1999; Moali et al 1998, 2000; Santhanam et al 2008).…”
Section: Model Formulationmentioning
confidence: 99%
“…Additionally there exist literature values for k C 1-IRrep , K C 1rep , K C 2 , K A 1 , and K i (Mansuy and Boucher 2004; Alarcón et al 2006; Boucher et al 1999; Moali et al 1998, 2000; Santhanam et al 2008). Literature values for the rate constants are found in Table 3.…”
Section: Model Formulationmentioning
confidence: 99%